Video Segmentation Techniques for Instructional Videos – Survey - Parsola, Jyoti; Gangodkar, Durgaprasad; Mittal, Ankush (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941724);" role="presentation">Low cost smart phones and easy internet access have caused an increase in viewership of e-<span dir="ltr" style="left: calc(var(–scale-factor)*460.54px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946961);" role="presentation">learning video. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93823);" role="presentation">Usually the memory size of mobile phones is less <span dir="ltr" style="left: calc(var(–scale-factor)*279.65px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906558);" role="presentation">therefore, <span dir="ltr" style="left: calc(var(–scale-factor)*321.67px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934462);" role="presentation">it becomes extremely important to reduce size of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.837016);" role="presentation">these <span dir="ltr" style="left: calc(var(–scale-factor)*96.14px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96146);" role="presentation">instructional videos. V<span dir="ltr" style="left: calc(var(–scale-factor)*189.41px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906075);" role="presentation">ideo segment<span dir="ltr" style="left: calc(var(–scale-factor)*243.65px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962548);" role="presentation">ation is <span dir="ltr" style="left: calc(var(–scale-factor)*277.73px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925896);" role="presentation">the fundamental task <span dir="ltr" style="left: calc(var(–scale-factor)*367.15px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*379.15px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953139);" role="presentation">reducing size of e-<span dir="ltr" style="left: calc(var(–scale-factor)*456.94px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934307);" role="presentation">learning videos. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927286);" role="presentation">This paper gives an overview of existing techniques <span dir="ltr" style="left: calc(var(–scale-factor)*286.37px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.841067);" role="presentation">used <span dir="ltr" style="left: calc(var(–scale-factor)*307.61px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929285);" role="presentation">for video segmentation of e-<span dir="ltr" style="left: calc(var(–scale-factor)*422.83px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922481);" role="presentation">learning videos. <span dir="ltr" style="left: calc(var(–scale-factor)*490.30px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95079);" role="presentation">Most <span dir="ltr" style="left: calc(var(–scale-factor)*513.82px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*88.10px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892071);" role="presentation">methods used <span dir="ltr" style="left: calc(var(–scale-factor)*147.86px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950437);" role="presentation">so far <span dir="ltr" style="left: calc(var(–scale-factor)*175.58px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950522);" role="presentation">for segmenting instructional video are <span dir="ltr" style="left: calc(var(–scale-factor)*337.03px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934112);" role="presentation">broadly <span dir="ltr" style="left: calc(var(–scale-factor)*371.23px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930006);" role="presentation">categorized into i<span dir="ltr" style="left: calc(var(–scale-factor)*443.38px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.18486);" role="presentation">) f<span dir="ltr" style="left: calc(var(–scale-factor)*453.82px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918425);" role="presentation">eature extraction <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890751);" role="presentation">based segmentati<span dir="ltr" style="left: calc(var(–scale-factor)*142.10px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914199);" role="presentation">on <span dir="ltr" style="left: calc(var(–scale-factor)*156.38px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.25088);" role="presentation">ii<span dir="ltr" style="left: calc(var(–scale-factor)*161.90px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06245);" role="presentation">) m<span dir="ltr" style="left: calc(var(–scale-factor)*177.02px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919122);" role="presentation">otion based segmentation. <span dir="ltr" style="left: calc(var(–scale-factor)*288.77px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929556);" role="presentation">The performance, comparative <span dir="ltr" style="left: calc(var(–scale-factor)*419.35px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913);" role="presentation">merits <span dir="ltr" style="left: calc(var(–scale-factor)*448.30px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.985873);" role="presentation">and limitations of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959244);" role="presentation">each approach is thoroughly exam<span dir="ltr" style="left: calc(var(–scale-factor)*218.09px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973445);" role="presentation">ined and contradicted. The analysis is beneficial <span dir="ltr" style="left: calc(var(–scale-factor)*428.95px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.982855);" role="presentation">for appropriate use of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895441);" role="presentation">ex<span dir="ltr" style="left: calc(var(–scale-factor)*81.38px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00582);" role="presentation">isti<span dir="ltr" style="left: calc(var(–scale-factor)*93.62px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900907);" role="presentation">ng methods and for enhancing <span dir="ltr" style="left: calc(var(–scale-factor)*217.61px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913402);" role="presentation">their performance or forming new methods on the basis of existing methods <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915749);" role="presentation">by combining one or two methods together